Magnetic penetration depth in the κ-(BEDT-TTF)2Cu[N(CN)2]Br organic superconductor. (2020) - Ait Ahmed, Y.; Tirbiyine, A.; Soubane, D.; Taoufik, A.; El Ouaddi, H.; El hamidi, H.; Abou Alhassan, A.; Hafid, A.; Senoussi, S.
Abstract: This paper systematically studied the magnetic penetration depth λ// (T) and superfluid density as a function of the cooling rate through the order–disorder transformation near 80 K for both the hydrogenated (κ-H8 -Br) and deuterated (κ-D8 -Br) κ-(BEDT-TTF)2 Cu[N(CN)2 ]Br organic superconductors. The magnetic penetration depth has been determined from the results of the dc magnetization measurements. The penetration depth was calculated near the critical temperature TC, our results show that the cooling of the samples at different rates through the order-disorder transformation near 80 K has a dramatic effect on the penetration depth, superfluid density and superconducting transition temperature TC .